Aplikasi Buku Saku Berbasis Android dalam Perubahan Perilaku Remaja Tentang HIV/AIDS di SMA N 16 Kota Padang - Silaban, Evi Maria Lestari (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2025)
Background. The situation of the spread of HIV/AIDS in Indonesia in 2019 shows that the cumulative number of HIV/AIDS cases is close to half a million or 500,000, namely 466,859 consisting of over 349,882 HIV and 116,997 AIDS. Aim. Determine the use of android-based pocket book applications in changing adolescent behavior about HIV/AIDS at SMA Negeri 16 Padang City. Method. This study is a quantitative research with a quasi experiment design and a one group pre test and post test approach. The data in this study were collected using a questionnaire and processed with univariate and bivariate with the Wilcoxon test. Result. The conclusion of the study is that android-based pocket book applications are effective in increasing adolescents' knowledge and attitudes about HIV/AIDS prevention. It is hoped that the pocket book application can be used as a reference and use sustainably and can be developed with more complete information according to the needs of the target.